2014
DOI: 10.14202/vetworld.2014.119-124
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and seasonal abundance of ticks on dogs and the role of Rhipicephalus sanguineus in transmitting Babesia species in Maidugiri, North-Eastern Nigeria

Abstract: Aim: An investigation on ticks and haemoparasites of dogs that belonged to Maiduguri metropolis (Borno State) was conducted. Materials and Methods:Survey of ticks and haemo-parasites on 400 stray dogs was conducted in Maiduguri from December 2009 to November 2011, using a stratified random sampling technique from different locations of the town. The town was divided into 10 districts out of which a total of 40 dogs were sampled at random from each district.Results: Four genera of ticks were identified on the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 8 publications
5
20
2
Order By: Relevance
“…Similarly, during the 2017 study period, a higher proportion (33.3%) of dogs older than 12 months were infested with ticks compared to dogs less than 12 months of age and the difference was statistically significant. This result is in contrast with a past study from Nigeria that reported dogs aged between 6-12 months were more susceptible to tick infestation (Konto et al, 2014). The reason for the higher tick infestation among older dogs in this study might be due to of older dogs being more mobile and likely to come more in contact with tick infested areas.…”
Section: Discussioncontrasting
confidence: 99%
“…Similarly, during the 2017 study period, a higher proportion (33.3%) of dogs older than 12 months were infested with ticks compared to dogs less than 12 months of age and the difference was statistically significant. This result is in contrast with a past study from Nigeria that reported dogs aged between 6-12 months were more susceptible to tick infestation (Konto et al, 2014). The reason for the higher tick infestation among older dogs in this study might be due to of older dogs being more mobile and likely to come more in contact with tick infested areas.…”
Section: Discussioncontrasting
confidence: 99%
“…Transmission of infestation between young and adults fowls may be due to intimacy between older ones and the young ones. Similar findings have been reported in other mammals [ 1 , 26 , 27 ].…”
Section: Discussionsupporting
confidence: 92%
“…Ticks are one of the most important ectoparasites of red jungle fowl. They are found attached to different parts of the body sucking blood and increasing the risk of infection to various microorganisms in humans and animals [ 1 - 3 ]. Clinically, they can be a nuisance; their bites can cause irritation and itching, accompanied by tissue and humoral reaction of the host, hyperemia, eosinophil infiltration, and a local edematous reaction [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, a gradual decline in parasite abundance was noticed from February to May, a period characterized by high temperature. Similar findings were reported in Nigeria (Shoorijeh et al, 2008;Arong et al, 2011;Konto et al, 2014).…”
Section: Discussionsupporting
confidence: 86%